MicroRNA-139-5p inhibits bladder cancer proliferation and self-renewal by targeting the Bmi1 oncogene - Hongbo Luo; Rui Yang; Chun Li; Yongqing Tong; Lingling Fan; Xiuheng Liu; Chuanrui Xu (Tumor Biology, 2017)
MiR-139-5p has been reported to be overexpressed in many types of cancers, but its role in bladder cancer has not been elucidated yet. Here, we report that miR-139-5p functions as a tumor suppressor in bladder cancer and inhibits the cancer stem cell self-renewal by targeting Bmi1 directly. We found that miR-139-5p expression was significantly downregulated in the bladder cancer specimens compared with that in adjacent normal tissues. In vitro, restoration of miR-139-5p expression significantly inhibited the proliferation of bladder cancer cells. Mechanism analysis revealed that miR-139-5p could decrease Bmi1 protein levels by binding to the 3′ untranslated region of Bmi1 messenger RNA. Stem cell–related proteins such as c-MYC, NANOG, OCT4, and KLF4 and signaling pathways such as Wnt signaling were suppressed by restoration of miR-139-5p in bladder cancer cells. In addition, miR-139-5p expression also blocked self-renewal of bladder cancer stem cells by inhibiting Bmi1. In summary, our study supports that miR-139-5p acts as a tumor suppressor in bladder cancer development and suppresses cancer stem cell property of bladder cancer. Our study also suggests that miR-139-5p has the potential to be used as a therapeutic molecule for bladder cancer treatment.